Changing Relations Between Fan Cultures and Industry: The Legitimation Paradox - Judith Fathallah (Journal of Management Practices, Humanities and Social Sciences, 2019)
The study aims to observe the deconstruction of the legitimation paradox at work, as the legitimacy of authorship itself begins to be questioned. It was most clear in metatextual styles of fanfic which reflected on its own relationship with the source text, and the showrunners' attempts at containment, which were then complicated by fandom's re-(re!)appropriation of control of the narrative, often with explicit reflection on the process. This article first explains the methodology that was developed, and makes the broader case for utilizing discourse analysis as a tool in studying fanwork. Using the cult television texts Sherlock (BBC), Game of Thrones (HBO) and Supernatural (CW) as a case study, discourse theory adapted from Foucault was utilized to establish that discursive formations from the source text can be de- and re-constructed, sometimes consolidating canon's constructions, but at other times, altering other characterizations and criticizing statements from canon. Multi-modal tools of fanvids, artwork, and even musical conventions have been utilized in the current study. The findings explained how changing media affordances of sites like Tumblr critique and undermine traditional conceptions of authorship and authority through their structure as modes of engagement as much as their content, and finally suggest some strategies of engagement for industry professionals.